Reversible data hiding in encrypted images with high payload - Dawen Xu (IET Information Security)
Abstract Reversible data hiding in encrypted images (RDH‐EI) can be used as an efficient technique to directly embed additional data in the encrypted domain without violating privacy. In this study, a multi‐MSB (most significant bit) prediction‐based RDH‐EI scheme is proposed, which is completely reversible and has high embedding payload. An improved gradient adjustment predictor (GAP) is used for pixel prediction. A binary location map is employed to store the location of the prediction errors. Subsequently, pre‐processing is performed on accurately predicted pixels in the original image to store the prediction difference. The pre‐processed image is encrypted using a stream cipher, and then the data hider can substitute multi‐MSB values of each available pixel in encrypted image with secret message bits to obtain the marked encrypted image. On the recipient side, the secret message can be extracted without any error and the original image can be reconstructed losslessly. Experimental results show that not only the embedding payload is improved but also the hidden data can be extracted accurately, and the cover image can be recovered perfectly.